Understanding the synergistic action of serum inflammatory markers and growth factors profile in excisional wound healing phases in rats’experimental model intraperitoneally treated with echinodermata glycosaminoglycans (GAGS) - Helmi, Nur Farihin Mohamad Helmi (2023)
Stichopus vastus; sea cucumbers, is a marine invertebrate which is rich in glycosaminoglycans (GAGs). This sea cucumber has long been utilised as traditional therapy alternatives, especially as wound healing remedy. The current study is designed in order to explore the effect of GAGs from integument wall of S. vastus species for wound healing properties in rats by intra-peritoneal injection with GAGs extract daily. Twenty-four (24) male Sprague Dawley rats were divided into four groups (n=6) which are control group; given phosphate buffer saline (PBS) and three treated groups of GAGs; at 2mg/kg, 4mg/kg and 6mg/kg body weight, respectively. Rats weight from 250-400 grams were treated with GAGs daily for 12 days. Skin graft and blood samples were taken for macroscopic and microscopic evaluation; while protein and gene expression of selected biomarkers (IL6, IL10, MMP-9, TNF-α, TGF- β1, VEGF-A, PDGF-A) were analysed with ELISA and qRT-PCR, respectively. In the macroscopic study, there was no significant difference (p>0.008) noted between all groups. Meanwhile, in the microscopic study, there were also no noted significant difference (p>0.008) between the groups in epithelialization, inflammation, fibroblast proliferation, collagen fibers organization and new vessels formation. However, via this research activities, it was revealed that, both either 2mg/kg or 4mg/kg of extracted glycosaminoglycans (GAGs) from S. vastus can enhance wound healing process at early phase of the wound healing when investigated macro and microscopically. In addition, in protein expression, the study disclosed that, there were significant difference (p<0.05) between treatment and control groups in IL-6, IL-10, MMP-9, VEGF-A and TNF-α while, there were no significant difference in PDGF-A and TGF- β1. On the other hand, gene expression study showed that, there were no significant difference (p>0.05) in all selected biomarkers. All in all, protein expression and gene expression revealed that, 2mg/kg of GAGs effects biomarkers: IL-6, IL-10, MMP-9 and VEGF-A, while 4mg/kg of GAGs effects biomarkers: TNF-α, PDGF-A and TGF- β1. GAGs extraction concentration selectively effects these biomarkers, as the wound healing cascade itself in a complex process. Extracted glycosaminoglycans (GAGs) from S. vastus have the potential to act as promoter for pro-inflammatory, antiinflammatory, anti-microbial effect on wound healing by targeting cytokines, chemokines and enzyme that participate in wound healing cascade to execute their pathophysiological roles. In this study the GAGs extraction concentration was observed to have selectively effects the biomarkers activities, however, as the wound healing cascade itself is actually a complex process, the pathway of this mechanism which consist of interactions of cytokines, chemokines and enzyme must be carefully investigated for further detail study.